2019
DOI: 10.1590/0004-282x20190043
|View full text |Cite
|
Sign up to set email alerts
|

Is the Mini-Mental State Examination the best cognitive screening test for less educated people?

Abstract: Mini-Mental State Examination (MMSE) results are strongly influenced by educational level. The Brief Cognitive Screening Battery (BCSB) is an alternative assessment tool that provides more accurate results in individuals with less education. Objective: Our aim was to compare the MMSE and BCSB as screening tests. Methods: The MMSE and BCSB were assessed in 112 participants by two evaluators blind to the other test's result. Participants were classified according to their level of education. The influence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…It took three minutes longer to apply the BCSB than to apply the MMSE. 27 The Recommendations of the Brazilian Academy of Neurology for the cognitive, functional, and behavioral assessment of Alzheimer disease was published in 2011 by Chaves et al 28 The BCSB was included among the tests to be employed in Brazil, as the FMT and semantic Verbal Fluency met the minimum validation requirements, having significant normative data and wide application in the Brazilian population. In that consensus meeting, it was commented that in spite of the wide application of the BCSB in Brazil, normative data for different age and education individuals were still needed.…”
Section: Influence Of Education Construct Validity and Normative Studiesmentioning
confidence: 99%
“…It took three minutes longer to apply the BCSB than to apply the MMSE. 27 The Recommendations of the Brazilian Academy of Neurology for the cognitive, functional, and behavioral assessment of Alzheimer disease was published in 2011 by Chaves et al 28 The BCSB was included among the tests to be employed in Brazil, as the FMT and semantic Verbal Fluency met the minimum validation requirements, having significant normative data and wide application in the Brazilian population. In that consensus meeting, it was commented that in spite of the wide application of the BCSB in Brazil, normative data for different age and education individuals were still needed.…”
Section: Influence Of Education Construct Validity and Normative Studiesmentioning
confidence: 99%
“…Although the results presented regarding the MMSE have been controlled in terms of age and education, the TMF stands out because it is an instrument that in itself has little influence on the education variable. [30][31][32] According to the ANOVA, however, the three clusters do not show any difference concerning the score results. Thus, we understand that although the groupings may differ in terms of global cognition, this difference does not appear to be due to mnemonic changes.…”
Section: Discussionmentioning
confidence: 90%
“…Small cross-sectional studies suggested that CDT is not sensitive enough to detect very mild dementia neither in educated people 7 nor in those with limited education. 5 Illiterate patients can be successfully screened for Alzheimer’s disease using well-known screening instruments in combined protocols (e.g., CDT and MMSE). 21 A study that analyzed the qualitative elements of CDT, rather than the sole score, showed that among participants without cognitive impairment, those with lower education often presented graphic difficulties, conceptual deficits, and spatial deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-item score Shulman system was considered as an accurate method for the widespread use in the diagnosis of dementia, requiring a substantial understanding of its scoring system. 6 In contrast, small cross-sectional studies suggested that CDT is not sensitive enough to detect very mild dementia neither in educated people 7 nor in those with limited education, 5 even though the CDT version employed in the last study had a complicated scoring system. Moreover, additional uses for the several CDT versions have been described in terms of evaluating the progression of cognitive decline, 8 differentiating types of dementia, 9 and even classifying qualitatively the elements of CDT according to the educational level.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation